2020
DOI: 10.3389/fcell.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Induces Epithelial Cell Unjamming

Abstract: The healthy and mature epithelial layer is ordinarily quiescent, non-migratory, solid-like, and jammed. However, in a variety of circumstances the layer transitions to a phase that is dynamic, migratory, fluid-like and unjammed. This has been demonstrated in the developing embryo, the developing avian airway, the epithelial layer reconstituted in vitro from asthmatic donors, wounding, and exposure to mechanical stress. Here we examine the extent to which ionizing radiation might similarly provoke epithelial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 69 publications
3
43
0
Order By: Relevance
“…While discovering the UJT marked by cellular motility in the experimental system (figure 1a), a novel metric-based on cell shape was proposed to predict UJT based on a theoretical computational model of epithelial cells (figure 1b). This cell shape elongation predicted by the theoretical model has been further validated in the experimental data [40,[58][59][60].…”
Section: Airway Epithelial Unjamming By Mechanical Compressionsupporting
confidence: 59%
See 2 more Smart Citations
“…While discovering the UJT marked by cellular motility in the experimental system (figure 1a), a novel metric-based on cell shape was proposed to predict UJT based on a theoretical computational model of epithelial cells (figure 1b). This cell shape elongation predicted by the theoretical model has been further validated in the experimental data [40,[58][59][60].…”
Section: Airway Epithelial Unjamming By Mechanical Compressionsupporting
confidence: 59%
“…10: 200254 the epithelial-to-mesenchymal transition (EMT) through the activation of the TGF-β receptor. However, signs of EMT were not observed during the UJT in HBE cells [59,61].…”
Section: Airway Epithelial Unjamming By Mechanical Compressionmentioning
confidence: 87%
See 1 more Smart Citation
“…But as the system progressively unjams and transitions to a fluid-like phase local rearrangements amongst neighboring cells become increasingly possible and tend to be cooperative, intermittent, and heterogeneous 46,[51][52][53][54] . While poorly understood, cellular jamming and unjamming have been identified in epithelial systems in vitro 37,39,43,46,48,49,[54][55][56] , in developmental systems in vivo 39,42,50,[57][58][59] , and have been linked to the pathobiology of asthma [37][38][39] and cancer 45,47,60,61 .…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] For example, experimental data from both in vitro [1][2][3]5,7,11,15 and in vivo 2,6 studies have shown that UJT occurs spontaneously during physiological events such as embryonic development 2,6,9 as well as during pathophysiological events including wound repair 1,16 and cancer metastasis 4,8,9,17,18 . In addition, stimuli such as radiation 19 , stretch 2 , and mechanical compression 2,11,15 , all of which are associated with lung diseases, also have the capacity to trigger UJT. In the jammed phase each cell becomes virtually frozen in place -trapped by its immediate neighbors-in a collective phase where intercellular rearrangements are rare.…”
Section: Introductionmentioning
confidence: 99%